Peningkatan Pengetahuan Masyarakat Melalui Edukasi Dalam Pencegahan ISPA Di Desa Cinta Rakyat Kecamatan Percut Sei Tuan - Aulia, Novi; Suhada, Herlisa (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
Abstract  Acute respiratory infections are a major cause of infectious disease morbidity and mortality worldwide. According to the World Health Organization, about 4 million people died from acute respiratory infections, 98% of which were caused by lower respiratory tract infections. Infant, child and elderly mortality rates are very high, especially in low- and middle-income countries. efforts to control ARI through health promotion education activities or counseling. Education is carried out with the aim of increasing knowledge and even the community is expected to be able to improve health status. The method in this service activity uses educational methods or counseling based on lecture discussions about ARI. The targets in this activity are mothers who have babies and children. Health problem factors, namely the habit of burning garbage can cause air pollution that comes from burning smoke in the environment and smoking habits.